Do Sources of Cigarettes Among Adolescents Vary by Age Over Time? - Lenk, Kathleen M. (2014)
Trends in sources of cigarettes among adolescents were assessed using data from a teen cohort (2000-2006). Five sources—bought from store, got from other teen, stole from others, bought from others, and got from an adult—were measured over time by age. The most common source among all ages was other teens. Fewer teens bought cigarettes from stores, with a downward trend for all ages. Among all ages there was an upward trend in stealing with younger teens more likely to steal cigarettes. In addition to targeting cigarette sales, interventions are needed to target other youth cigarette sources.